2010
DOI: 10.1080/15389588.2010.489198
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helmet Use Among Motorcycle Users in Tamale Metropolis, Ghana: An Observational Study

Abstract: Objective: To estimate the prevalence of helmet use among riders and pillion riders of motorcycles in the Tamale Metropolis of Ghana.Methods: Cross-sectional observations of helmet use were made at locations where traffic generally slowed down. Statistical analysis was carried out for variables by calculating chi-square (χ 2 ) tests to assess statistical significance.Results: A total of 3115 riders and 1058 pillion riders (passengers) were observed at 10 different sites. The overall helmet use for riders was 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
44
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 14 publications
8
44
1
Order By: Relevance
“…Safety helmet use rates of 16.3% and 13.2% were observed for male and female child pillion riders, respectively. The reported safety helmet use compliance rate [8] for riders is higher than that of the child pillion riders' as in accordance with other studies [9,10,11]. A majority of Malaysian population is aware of the safety helmet law, however the compliance rate is still low among child pillion riders [8].…”
Section: Introductionsupporting
confidence: 72%
“…Safety helmet use rates of 16.3% and 13.2% were observed for male and female child pillion riders, respectively. The reported safety helmet use compliance rate [8] for riders is higher than that of the child pillion riders' as in accordance with other studies [9,10,11]. A majority of Malaysian population is aware of the safety helmet law, however the compliance rate is still low among child pillion riders [8].…”
Section: Introductionsupporting
confidence: 72%
“…These factors are both of a personal and contextual nature. Among the former, it has been observed that women tend to use helmets more than men (Ledesma, Peltzer, Po o, & Cremonte, 2010;Papadakaki et al, 2013;Skalkidou et al, 1999), that drivers use helmets more than passengers (Ackaah & Afukaar, 2010;Bachani et al, 2012;Ledesma et al, 2010), and that comfort, aesthetic reasons and peer pressure influence helmetuse decisions (Conrad, Bradshaw, Lamsudin, Kasniyah, & Costello, 1996;Germeni, Lionis, Davou, & Petridou, 2009;Zamani-Alavijeh et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…When riders detect the presence of the police on the road, motorcyclists use unconventional paths to circumvent the police roadblocks to avoid going through routine checks. By indulging in this behaviour, motorcyclists in Northern Ghana avoid the police and violate road traffic rules such as using unregistered vehicles (Kudebong et al, 2011) and not wearing helmets (Ackaah & Afukaar, 2010;Akaateba, Amoh-Gyimah, & Yakubu, 2014). For cyclists, the situation is more problematic.…”
Section: Discussionmentioning
confidence: 97%
“…This is due to the fact that bicyclists and motorcyclists are less likely to wear helmets in Northern Ghana (Ackaah & Afukaar, 2010;Akaateba et al, 2014;Kudebong et al, 2011). Thus, in the event of a crash, twowheeler riders are exposed to severe head injuries which limit their chances of survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation